An investigation of parental involvement in the development of their children's literacy in a rural Namibian school - Siririka, Gisela (Rhodes University, Faculty of Education, Department of Education, 2007)
This study sought to investigate the involvement of parents in the development of their children's literacy. The study was conducted in a rural school in the Omaheke region of Namibia, a school selected for reasons of representativeness and convenience. The research took the form of an interpretive case study focussing on a study sample of nine parents, their children, and one teacher in the Ngeama community. Data were collected through semi-structured interviews and then subjected to comprehensive descriptive analysis. The findings of the study indicate that parents in the Ngeama rural community have not been effectively involved in their children's acquisition of literacy, for a number of reasons. These include the parents' not feeling appropriately empowered to influence the development of their children's literacy, the absence of environmental literacy programmes within the community, and the shortage of literacy materials such as newspapers and magazines. Perhaps the most important factor is that there is no public or school library in the Ngeama community. In view of these findings, the study recognizes a need for parental empowerment in terms of knowledge, skills, understanding and resources allocation regarding the education of their children. It recommends that a relationship of trust and understanding be built between the school and the community to ensure the sound development of literacy skills. The study further recommends the establishment of a library in order to enhance the literacy levels of teachers, parents and children alike.
Keywords: Education -- Namibia; Education -- Parent participation -- Namibia; Rural schools -- Namibia; Community and school -- Namibia; Literacy -- Social aspects -- Namibia; Literacy -- Study and teaching -- Namibia; Libraries and education -- Namibia